Challenges faced by undergraduate students in Mandarin language ODL during Movement Control Order period / Chin Jing Ru ... [et al.] - Jing Ru, Chin; Yang Lian, Tay; Yusof, Johana; Mei Yit, Yeong (Universiti Teknologi MARA Perak, 2021)
Due to the implementation of Movement Control Order (MCO) caused by the COVID-19 pandemic, the transformation from traditional face-to-face classes to the Open and Distance Learning (ODL) mode has affected basic Mandarin learners in higher learning institutions. After studying Mandarin level 1 through face-to-face classes for only three weeks, students were forced to adjust and adapt to ODL within a short period of time. This situation had posed challenges on both lecturers and students that had also affected their teaching and learning quality during the MCO period. While lecturers are required to put in intensive effort and time to design teaching materials, students also need to equip themselves with sufficient technical proficiency to decode and comprehend the course materials. Hence, a study on the challenges faced by students during the ODL mode under this circumstance is crucial to establish a better understanding on the possibility of ODL’s sustainability as a necessary component in learning Mandarin henceforward. A questionnaire was designed for this study to survey different criteria of challenges, namely adaptability struggles, technical issues, computer literacy, time management, and self-motivation. By identifying the challenges faced by students in ODL and providing solutions through proper initiatives, it will help to apprehend and further satisfy students’ needs in studying Mandarin through the ODL mode.